Optimalisasi Kompetensi Guru dalam Penerapan PjBL Berbasis STEM melalui IHT - Endang P Handayani; Syahrial Ayub (Journal of Education, Science, Geology, and Geophysics (GeoScienceEdu), 2021)
This research aims to optimize teacher competence in implementing STEM-based PjBL through In House Training (IHT) by integrating school action research for teacher teachers in SD Negeri 6 Mataram. Research is conducted in 2 cycles with each cycle through the stages of planning, implementation and observation, evaluation and reflection. The research sample was a teacher of State Elementary School 6 Mataram which amounted to 10 people. The research began with STEM-based PjBL modeling, discussion of STEM-based PjBL learning and syntactic structures, STEM-based PjBL RPP design, and classroom application. These activities are integrated in the design of classroom action research. The results showed that In House Training (IHT) activities at SD Negeri 6 Mataram against teachers with the integration of school action research effectively improved teacher competence in implementing STEM-based PjBL.